2008
DOI: 10.1111/j.1600-0579.2007.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the oral healthcare team in countries with emerging economies

Abstract: Health is a critical dimension of human well‐being and flourishing, and oral health is an integral component of health: one is not healthy without oral health. Significant barriers exist to ensuring the world’s people receive basic healthcare, including oral healthcare. Amongst these are poverty, ignorance, inadequate financial resources and lack of adequate numbers of educated and trained (oral) healthcare workers. Emerging economies are encouraged to develop a national strategic plan for oral health. Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
1
28
0
2
Order By: Relevance
“…A recent study investigated the performance of dental amalgam comparative with dental composite in extensive posterior restorations [30]. Different risk factors for restoration failure like age, sex, alcohol consumption, smoking, diabetes, periodontal status and also matrix metalloproteinase genetic polymorphisms were analysed [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Data obtained from this study showed similar rates of failure for amalgam and composites up to 5 years, the authors concluding that resin composites could replace amalgam for posterior extensive restorations.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigated the performance of dental amalgam comparative with dental composite in extensive posterior restorations [30]. Different risk factors for restoration failure like age, sex, alcohol consumption, smoking, diabetes, periodontal status and also matrix metalloproteinase genetic polymorphisms were analysed [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Data obtained from this study showed similar rates of failure for amalgam and composites up to 5 years, the authors concluding that resin composites could replace amalgam for posterior extensive restorations.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive analysis showed some universal characteristics of dentists' population elsewhere: predominance of women , high levels of professional involvement ( dentistry as main occupation and high weekly workload ), predominance of workers in private dental service , and a tendency toward specialization and concentration in large cities [4,5,10]. Bravo-Péres [1] found a similar situation in Spain in 2004 and Brown and Lazar [14] described how, in the United States of America, the decline in private practice started at the beginning of the 1990 s. In Brazil, a similar situation occurred at the same time when there was an increased demand and utilization of public dental services.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies underlined recommendations for a strategic national oral health care plan for countries with both developed [4] and emerging economies [5]. The recent Brazilian national curriculum guidelines for university dental courses are consistent with public health policies, which emphasize the need for general dental practitioners focused on primary oral health care, with the ability to cooperate across different professional disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the allocation of human resources, it is necessary to develop prognostic models that incorporate demand for dental services as well. [13][14][15][16] Since the beginning of the 1980s, the increase in the number of dentists in some countries has led their governments to take measures to curtail the number of new students and to close dental schools. In other countries, no measures have been taken.…”
mentioning
confidence: 99%